A non-contact broad bandwidth current sensor. (1st October 2022) - Zhang, Rui; Zhang, Qiaogen; Geng, Jiangtao; Liu, Fuli
Abstract: Power metering, relay protection, lightning current measurement, fault current measurement, and traveling current measurement in the field of power systems, as well as high-current measurement in the field of pulse power, require safe, high-accuracy, large-range, and wide-frequency-band current sensors. Current transformers and Rogowski coils can basically meet the requirements of measurement accuracy and range, but they are not good enough to meet the two requirements of safety and broad frequency bands. In this study, a non-contact broad-band current sensor is designed, which is based on the improvement of the traditional Rogowski coil to realize non-contact measurement of current. The equivalent circuit of the sensor was established, and the output characteristics of the sensor were calculated from the theoretical level as well as the design parameters were optimized. The sensor samples were made, and the usability of the sensor and the correctness of the theoretical calculation model were verified by 50 Hz AC current and 1.6 μs/3.4 μs impulse current tests. The non-contact current sensor designed in this paper has the advantages of simple structure, low cost, safety and reliability, large range, and wide operating band, and can be widely used for AC current or impulse current measurement in power systems and pulsed power fields.